Instilling The Character of Nationality Through Pancasila Strengthening Model in Early Childhood - Samiaji, Mukhamad Hamid; Prawening, Cesilia; Tri Mulyani, Chandra (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2025)
Planting character love of the motherland since early is step strategic in to form generation thathas nationalism and love towards Indonesia. In children age early on, the values of Pancasila can appliedthrough a simple approach however impressive, like activity play, stories, and interactions social.Problems regarding the decline attitude nationalism no can left alone so only. Furthermore, earlychildhood education is considered only for read and write just whereas important apply child - centeredand learning projects while playing outside a class that fosters Pancasila values since age early throughinterest child. So from that, this research use methodology qualitative type studies case with techniquedata collection in the form of observation, interviews, and documentation that describes how to plantlove of the motherland and nationality through the pancasila strengthening model for children age early.This research utilise method Miles and Huberman's interactive data model analysis in the form of datacollection, data reduction, data presentation, description, and conclusion. Results of the study put intopractice as a model for strengthening Pancasila in children age early, especially character Love of themotherland and nationality.